"Salida de la Columna Garcia Oliver al frente de Aragon. En el centro: Ricardo Sanz". At the Bakunin barracks. Copied from CNT collection
"Salida de la Columna Garcia Oliver al frente de Aragon. En el centro: Ricardo Sanz". At the Bakunin barracks. Copied from CNT collection.